Self-cleaning as a defence to exclusions for misconduct: an emerging concept in EC public procurement law? - Arrowsmith, Sue; Priess, Hans-Joachim; Friton, Pascal (Sweet and Maxwell, 2009)
The EU procurement directives provide for both discretionary and mandatory exclusions from EU public contracts of suppliers convicted of criminal offences or involved in gross misconduct. This article seeks to demonstrate that, although it is not stated expressly in the directives, it is a legal requirement to recognise as a defence to exclusion that the supplier concerned has undertaken self-cleaning measures to prevent a repetition of the conduct concerned.